Two shell middens as indicators of shellfish exploitation patterns during the first millennium AD on the Natal north coast - Horwitz, L.; Maggs, T.; Ward, V. (Southern African Humanities, 2021)
Two large coastal middens dating mainly to the first millennium AD, with some later material, are described. They contain complete sequences of Early Iron Age ceramics but otherwise only a very restricted range of faunal remains heavily dominated by the brown mussel (Perna perna). The changing function of the middens is discussed in relation to shellfish exploitation, its impact on the local shellfish population and the possible relationship between midden and inland village sites of the same period. The evidence indicates that excessive levels of harvesting did not take place. The possibility that the middens served villages more than 20 km inland is the subject of further research. To cite this article: Horwitz, L., Maggs, T. & Ward, V. 1991. Two shell middens as indicators of shellfish exploitation patterns during the first millennium AD on the Natal north coast. Natal Museum Journal of Humanities 3: 1-28.